Film Dokumenter Kehidupan Sosial Anak Asuhan Menggunakan Teknik Sinematik - Elzar Nataniel Kalombak Parammak; Yusni Nyura; Damar Nucahyono (JURNAL VOKASI TEKNIK, 2024)
This research explores the social life of orphaned children in Samarinda City, wherefoster children have problems such as sexual harassment, domestic violence (KDRT), children of disaster victims, and neglected children. Therefore. This research will make a documentary film using Cinematic Techniques with the title Documentary Film on the Social Life of Foster Children. This Research will explore the lives of children in foster care, presenting an in-depth picture of social dynamics, internal conflicts, and the search for urban identity. In making this documentary, we used the Adobe Premiere Pro application for video editing. The aim of this research is to create aesthetic shots and improve image quality through cinematic techniques and convey messages about the social life of orphaned children in documentary films. The process of making a documentary film consists of pre production, production, post production and post distribution stages using cinematic techniques, which include the principles of Extreme Long Shot, Long Shot, Medium Long Shot, Close Up, and Medium Shot. the results of this research are a documentary film about the lives of children in foster care. Which has been uploaded to the youtube page https://www.youtube.com/watch?v=4WMW_MuSRVU&t=21s, with 1.500 views, 3 likes, subscribers 358.